Calculating the Cost of Co2e Emitted to Generate the Required Electricity: Case Study of Lecture Rooms in the Faculty of Engineering- Universiti Putra Malaysia. - Mohd Yusuff, Rosnah; Shahmohammadi, M. Sadegh; Houshyar, A. Noori (2013)
Malaysia is endowed with abundant supplies of non-renewable energy resources, especially oil and gas. However, its current oil and gas reserves are expected to be depleted within the next few years. If new oil fields are not found, Malaysia will have its oil depleted around 2030.Malaysia has actively participated and involved in key conventions regarding environment and sustainable development, such as Montreal Protocol and Kyoto Protocol. University Putra Malaysia (UPM) as one of the largest universities in Malaysia should try to make its energy consumption as efficient as possible and Faculty of Engineering may be the pioneer in this regard. As the result of this study we can see that only for generating the required electricity for the eight lecture rooms at faculty of engineering about RM 45 per day is the cost of Co2e emissions. In this study authors will calculate the cost of Co2e Emitted to Generate the Required Electricity for the Lecture Rooms in the Faculty of Engineering of Universiti Putra Malaysia.